Inhibition of Mitochondrial p53 Accumulation by PFT-μ Prevents Cisplatin-Induced Peripheral Neuropathy - Maj, Magdalena A.; Ma, Jiacheng; Krukowski, Karen N.; Kavelaars, Annemieke; Heijnen, Cobi J. (Frontiers in Molecular Neuroscience, 2017)
Chemotherapy-induced peripheral neuropathy (CIPN), a debilitating major side effect of cancer treatment, is characterized by pain and sensory loss in hand and feet. Platinum-based chemotherapeutics like cisplatin frequently induce CIPN. The molecular mechanism underlying these neurotoxic symptoms is incompletely understood and there are no preventive or curative interventions. We hypothesized that cisplatin acts as a cellular stressor that triggers p53 accumulation at mitochondria, leading to mitochondrial dysfunction and CIPN. To test this hypothesis, we examined the effect of the small molecule pifithrin-µ (PFT-µ), an inhibitor of p53 mitochondrial association on CIPN and the associated mitochondrial dysfunction. We show here for the first time that in vivo cisplatin rapidly increases mitochondrial accumulation of p53 in dorsal root ganglia (DRG), spinal cord and peripheral nerve without evidence for apoptosis. Cisplatin-treatment also reduced mitochondrial membrane potential and lead to abnormal mitochondrial morphology and impaired mitochondrial function in DRG neurons. Pre-treatment with PFT-µ prevented the early cisplatin-induced increase in mitochondrial p53 and the reduction in mitochondrial membrane potential. Inhibition of the early mitochondrial p53 accumulation by PFT-µ also prevented the abnormalities in mitochondrial morphology and mitochondrial bioenergetics (reduced oxygen consumption rate, maximum respiratory capacity, and adenosine triphosphate synthesis) that develop in DRG and peripheral nerve after cisplatin-treatment. Functionally, inhibition of mitochondrial p53 accumulation prevented the hallmarks of CIPN including mechanical allodynia, peripheral sensory loss (numbness) as quantified by an adhesive-removal task, and loss of intra-epidermal nerve fibers. In conclusion, PFT-μ is a potential neuroprotective agent that prevents cisplatin-induced mitochondrial dysfunction in DRG and peripheral nerves thereby protecting against CIPN through blockade of the early cisplatin-induced increase in mitochondrial p53. Notably, there is accumulating evidence that PFT-µ has anti-tumor activities and could therefore be an attractive candidate to prevent CIPN while promoting tumor cell death.